Стратегічні комунікації в діяльності органів прокуратури: актуальні особливості та напрямки вдосконалення - Музичук, О. М.; Muzychuk, O. M. (Право.ua. - 2023. - № 4. - С. 24-30, 2023)
Визначено актуальні особливості та напрямки вдосконалення стратегічних комунікацій у діяльності прокуратури. Розкрито сутність стратегічних комунікацій, окреслено специфіку процесу управління стратегічними комунікаціями в умовах воєнного стану. З урахуванням інноваційних аспектів світового комунікативного простору виокремлено особливості стратегічних комунікацій у діяльності прокуратури, а також напрямки вдосконалення такої діяльності.

The article emphasizes the fact that strategic communications in the modern information and digital environment, in which information exchange is currently taking place, are the basis for the effective functioning of any organization. It is noted that the domestic experience of the functioning of state institutions in the conditions of the Russian-Ukrainian war indicates a deep restructuring of the elements of strategic communications in accordance with new security challenges, as well as the leading role of control over information processes in the conditions of informational and psychological warfare. At the same time, it was emphasized that in the field of activity of the prosecutor’s office in Ukraine, in terms of strategic communications, innovative aspects of the global communication space should be considered, the development of which in modern realities is largely based on digitization, the development of artificial intelligence, as well as the worldview aspects of postmodern society. It is substantiated that the deep essence of any activity, including strategic communications in the activities of the prosecutor’s office, is revealed in the set of its signs, in particular those of them that are specific, generated by the latest vision and evolutionary restructuring of social relations. The first feature highlighted in the works of foreign researchers is the relationship and mutual influence between strategic ambiguity and strategic ambiguity. The second feature of strategic communications, which is dictated by scientific and technical progress and the restructuring of human thinking in postmodern conditions, is the increasing visualization of strategic communications. The third feature of modern strategic communications comes down to the appropriate system of moral and ethical values, which is an integral part of crisis communication in terms of ensuring reliability, truthfulness, fairness, accountability and transparency. On the basis of the signs of strategic communications in the activity of the prosecutor’s office identified by us, directions for improvement of such activity are identified, which determine the foundations of the development of strategic communications in the activity of the prosecutor’s office. Attention is focused on the need for a strategic vision of building not only sustainable, but also effective communication, which is carried out to maintain national security in the conditions of martial law, as well as conducting further interdisciplinary research on a wide range of aspects of the development of strategic communications in the activities of the prosecutor’s office, in particular, the potential for the application of elements artificial intelligence in this field, as well as the international dimension of strategic communications.

Определены актуальные особенности и направления усовершенствования стратегических коммуникаций в деятельности прокуратуры. Раскрыта сущность стратегических коммуникаций, очерчена специфика процесса управления стратегическими коммуникациями в условиях военного положения. С учетом инновационных аспектов мирового коммуникативного пространства выделены особенности стратегических коммуникаций в деятельности прокуратуры, а также направления совершенствования такой деятельности.
Strategic communications in the activities of the prosecutor’s office: current features and directions for improvement
Keywords: органи прокуратури; національна безпека; стратегічні комунікації; державне управління; громадянське суспільство; воєнний стан; штучний інтелект; prosecutor’s office; national security; strategic communications; public administration; civil society; martial law; artificial intelligence; органы прокуратуры; национальная безопасность; стратегические коммуникации; государственное управление; гражданское общество; военное состояние; искусственный интеллект